THE INFLUENCE OF SOCIO-ECONOMIC FACTORS ON CORN FARMERS' INCOME (Sama Rasa Farmers Group in Oesao Subdistrict, East Kupang District, Kupang Regency) - Letetia Rosario G Udjan; Tomycho Olviana; Paulus Un (Undana Press, 2026)
This study aims to: 1) Determine the income of corn farmers, 2) Determine the influence of socio-economic factors on the income of corn farmers in the Sama Rasa Farmers Group, Oesao Village, East Kupang Sub-district, Kupang Regency. The location was deliberately (purposively) chosen in Oesao Village, East Kupang Sub-district, Kupang Regency. The population consists of 36 farmers. The sample was determined using the total sampling technique, resulting in a sample of 36 farmers. The type of data used is quantitative data with income analysis and multiple linear regression analysis to answer the influence of socio-economic factors on corn income. The results of the study showed that the average corn production per farmer was 1,406.2 kg and the average production per hectare was 1,181.4 kg. The average income per corn farmer was IDR 7,469,372 and the average income per hectare was IDR 63,753,208. Of the seven socio-economic factors, there are four socio-economic factors that are It has a very significant effect on corn income, namely land area, capital, labor, and education level. Meanwhile, the three variables that do not have a significant effect on corn income are age, family dependents, and marital status. The agricultural sector has a very important and strategic role in providing staple food and employment opportunities, and it also becomes a driver for economic growth for the community, especially in the Oesao Sub-district of Kupang Regency. In East Kupang Regency, Oesao Sub-district is one of the areas that produces a substantial amount of corn, considering that this area has a climate, type of soil, and land area suitable for this crop. The goal of development is not only to increase income. Efforts to increase income are very important but do not occur independently.